Biochemical Evaluation of Fendo - Ehadi A. I. Elkhalil; Misaa Ali Almhadi Ahmed; Huda Osman (Food Studies: An Interdisciplinary Journal, 2026)
Malnutrition and micronutrient deficiencies, including iodine deficiency disorders (IDD), remain critical health challenges in Darfur, Sudan. Traditional, underutilized foods such as fendo (a fermented locust-based product) offer a promising, culturally accepted dietary solution. This study aimed to evaluate the nutritional composition, protein digestibility, and antinutritional factors of fendo made from two locust species (tree and desert locusts) and to assess the effect of furundu (fermented hibiscus seed) supplementation on its nutritional quality, with particular focus on iodine enrichment. Fendo was prepared from fermented tree and desert locusts, with and without furundu supplementation at 5%, 10%, and 15%. The treatments were analyzed for moisture, ash, protein, fat, fiber, carbohydrates, in vitro protein digestibility (IVPD), tannins, phytates, and iodine content. Data collected from different treatments were subjected to analysis of variance (ANOVA) test using SPSS, version 22; the means were separated using Duncan’s multiple range test. Fermentation significantly enhanced protein (up to 68.60%), fat, and IVPD (up to 70.90%), while reducing fiber, carbohydrates, tannins, and phytates. Supplementation with 15% furundu further improved IVPD (up to 84.61%) and significantly increased iodine content (up to 1,570 µg/100 g), surpassing the recommended daily intake. Antinutritional factors remained well below previously reported levels, suggesting improved nutrient bioavailability. Fendo, especially when supplemented with furundu, demonstrates strong potential as a nutrient-dense, shelf-stable, and culturally acceptable food product. It could serve as a functional food intervention to address protein–energy malnutrition and iodine deficiency in Darfur and similar food-insecure regions. The revitalization and promotion of traditional fermented foods such as fendo may contribute meaningfully to regional food security and public health strategies.